'Creating a Buzz'. (2nd November 2020) - Hempsall, James
Abstract : James Hempsall reports on important lessons learned from establishing speech, language and communication project Talk Derby. Funded by DfE Opportunity Areas, it has laid the foundations for an ongoing strategy which fuels networking and training, supported by local authority involvement.